Two-Dimensional Convolution Algorithm for Modelling Multiservice Networks with Overflow Traffic. (10th June 2013) - Głąbowski, Mariusz; Kaliszan, Adam; Stasiak, Maciej
Abstract : The present paper proposes a new method for analytical modelling multiservice networks with implemented traffic overflow mechanisms. The basis for the proposed method is a special two-dimensional convolution algorithm that enables determination of the occupancy distribution and the blocking probability in network systems in which traffic streams of individual classes can be serviced by both primary and alternative resources. The algorithm worked out by the authors makes it possible to model systems with any type of traffic offered to primary resources. In order to estimate the accuracy of the proposed method, the analytical results of blocking probabilities in selected networks with traffic overflow have been compared with simulation data.